Uporabnost maščobnih kislin omega-3 pri obravnavi ran na koži - Vrbnjak, Dominika (Obzornik zdravstvene nege, 2015)
Introduction: The purpose of this article is to analyse the effect of omega-3 fatty acids on wound healing and to demonstrate their usefulness in the wound treatment. Methods: Databases PubMed, CINAHL, Medline and ScienceDirect were searched for the literature review and analysis. A search was performed with keywords in English: omega-3 fish oil, polyunsaturated fatty acid (PUFA), wound, wound healing, and Boolean operator AND. Experimental or randomized clinical studies published in English from 1993 to January 2014, which included the prevention or treatment of acute skin wounds or chronic wounds by using omega-3 fatty acids, were included in analysis. Exclusion criterion was the use of omega-3 fatty acids in the treatment of burn wounds. From a total of 1151 retrieved studies, 15 were included in a detailed analysis. Results: The results showed that omega-3 fatty acids are ineffective in the treatment of traumatic and surgical skin wounds, potentially effective in the treatment of diabetic wounds and effective in the treatment of pressure ulcers. Discussion and conclusion: Anti-inflammatory effect of omega-3 interferes and slows down acute skin wound healing, but promotes the reepitalization of chronic wounds. Further research is required to establish exact wound care use guidelines.
Keywords: acute wound; akutna rana; celjenje; chronic wound; healing; kronična rana; maščobne kisline; nenasičene maščobne kisline; rane; unsaturated fatty acids